2016
DOI: 10.1186/s12879-016-2037-6
|View full text |Cite
|
Sign up to set email alerts
|

Community-based interventions to enhance knowledge, protective attitudes and behaviors towards canine rabies: results from a health communication intervention study in Guangxi, China

Abstract: BackgroundIn China canine rabies poses a serious public health problem in that human mortality ranks the second highest globally. While rabies health education interventions are advocated by WHO to be critical components of modern rabies control and prevention programs, available studies have not adequately investigated the relative efficacy of their implementation in at-risk populations. This study aims to measure and compare the effect on knowledge and protective behavior towards rabies of health education i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
12
1
1
Order By: Relevance
“…This finding may be because people are more accepting of the information through mobile SMS and might have read the information repeatedly. This result is closely similar to a study in China that explored different communication interventions to improve rabies-related KAP and reported that combining SMS and regular information sessions can produce better effects [23]. The result is also in accordance with a field experiment conducted in Peru which reported that positive changes were seen in household behavior when exposure of preventive health information related to dengue was given through mobile phones in order to study participants’ responses and reactions [14].…”
Section: Discussionsupporting
confidence: 87%
“…This finding may be because people are more accepting of the information through mobile SMS and might have read the information repeatedly. This result is closely similar to a study in China that explored different communication interventions to improve rabies-related KAP and reported that combining SMS and regular information sessions can produce better effects [23]. The result is also in accordance with a field experiment conducted in Peru which reported that positive changes were seen in household behavior when exposure of preventive health information related to dengue was given through mobile phones in order to study participants’ responses and reactions [14].…”
Section: Discussionsupporting
confidence: 87%
“…The reasons that cases did not receive recommended PEP after exposure were not investigated in our study, it may be related to several factors, such as the prohibitive costs of vaccine and RIG, the lack of awareness about necessity of PEP and inadequate access to vaccine and RIG in primary health services especially in rural areas [ 25 ] (see Additional file 1 : Supporting file 6 for details). Therefore, appropriate actions should be implemented and strengthened including (1) increase subsidies for rabies medication by expanding the scope of medical insurance for rabies PEP, just as some high-incidence human rabies provinces in China like Hunan and Guangdong, which have included rabies PEP expenditures into the new rural cooperative medical reimbursement coverage, (2) educate the public on the need of rapid treatment post exposure [ 26 ] and use education approaches such as short-message-service or WeChat, which might be useful tools for health promotion [ 27 ], (3) educate public health workers to evaluate and identify potential exposures to rabies and provide adequate PEP [ 28 ], (4) establish “animal bite treatment centers” in rural areas for better treatment and surveillance of rabies and animal bites in Chongqing.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have shown increases in rabies-awareness and more specific knowledge related to rabies and dog bite treatment using a variety of different educational methods. These include a 1 h educational intervention for school children in Sikkim, India (1), a curriculum integration program for elementary school children in El Nido, Philippines (2), rabies education information sessions and rabies information text messages in China (3), an “edutainment” campaign for schoolchildren in Sri Lanka (4) and an awareness campaign using posters, leaflets and text messages in Azerbaijan (5). However, in most of these studies, the assessment of knowledge increases was conducted over a very short timescale (days to months), and it is unclear how long this knowledge was retained, or whether it resulted in any change in behavior regarding the disease.…”
Section: Introductionmentioning
confidence: 99%